Епіфітні бріоугруповання ландшафтного заказника «Чорноліський» (Кіровоградська обл.) - Гапон, С.В. (Український ботанічний журнал, 2009)
Изучен эпифитный моховой покров государственного ландшафтного заказника «Чернолесский» (Кировоградская обл.). Дана флористическая и ценотическая характеристика восьми ассоциаций и трех бриосообществ, определено их синтаксономическое положение. Впервые для Украины приводятся Plagiomnio cuspidate—Homalietum trichomanoidis (Pec. 1965) Mast. 1993, Madotheco platyphyllae—Leskeelletum nervosa (Gams 1927) Barkm. 1958. The epiphytic moss cover of the Chornoliskiy Landcape Preserve (Kirovograd Region) was studied. The floristic and coenotic characteristics of 8 associations and 3 moss communities and their syn taxo nomic positions are given. The syntyaxa Plagiomnio cuspidate—Homalietum trichomanoidis (Pec. 1965) Mast. 1993, Madotheco platyphyllae—Leskeelletum nervosae (Gams 1927) Barkm. 1958 are re ported for the first time for Ukraine.